Analysis of factors affecting injury severity for riders or occupants of all-terrain vehicles and golf carts involved in police-reported crashes. (December 2019) - Russo, Brendan J.; Smaglik, Edward J.
Highlights: Factors affecting severity of ATV and golf cart crashes were investigated. Random parameters ordered logit model was estimated to analyze injury severity. Alcohol or drug use significantly increased probability of severe injuries. Riding an ATV was associated with more severe injuries compared with golf carts. Safety device use and paved roads were associated with less severe injury outcomes. Abstract: In recent years, the popularity of all-terrain vehicles (ATVs) in the United States (US) has increased, and the number of ATV driver and passenger deaths have also increased substantially in the last few decades. Riders or occupants of ATVs as well as golf carts are particularly vulnerable to injury, not only due to the lack of protection and safety equipment offered by their vehicles, but also the propensity for ejection in the event of a crash. Given the vulnerability of these road users, it's critical to understand factors which may affect injury severity to plan effective countermeasures aimed at reducing these injuries and fatalities. To better understand factors affecting the injury severity of ATV and golf cart riders or occupants involved in police-reported crashes, this study presents an analysis using six years of crash data from the US state of Arizona. Over the analysis period, there were 1769 drivers/passengers of these vehicle types involved in police-reported crashes. Of these occupants/riders, 67.7% were injured or killed as a result of the crash; a proportion significantly higher than police-reported crashes involving most other vehicle types, exhibiting the need to examine factors leading to these injuries and fatalities. In order to analyse factors affecting the injury severity of ATV and golf cart occupants/riders, a random parameters (RP) ordered logit statistical model was developed, which was most appropriate given the ordered nature of injury-severity data. Several person- vehicle- roadway- and environmental-related variables were found to significantly affect the injury severity of riders or occupants of ATVs and golf carts. Given the vulnerability of these road users, it's important for transportation agencies to explore effective countermeasures aimed at reducing the severity of crashes involving these vehicle types. The results of this study provide important insights which can assist in developing effective engineering-, enforcement-, education, or policy-related countermeasures.